2021
DOI: 10.7554/elife.65096
|View full text |Cite
|
Sign up to set email alerts
|

Linguistic processing of task-irrelevant speech at a cocktail party

Abstract: Paying attention to one speaker in noisy environments can be extremely difficult, because to-be-attended and task-irrelevant speech compete for processing resources. We tested whether this competition is restricted to acoustic-phonetic interference or if it extends to competition for linguistic processing as well. Neural activity was recorded using Magnetoencephalography as human participants were instructed to attended to natural speech presented to one ear, and task-irrelevant stimuli were presented to the o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
36
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 155 publications
(265 reference statements)
10
36
0
Order By: Relevance
“…Other studies also confirmed the recognition of some words from a background speech stream, even if the background consisted of multiple voices (Dekerle et al, 2014). Furthermore, signs of spectro-temporal and linguistic processing of task-irrelevant speech streams were found in the auditory cortex, left inferior cortex, and posterior parietal cortex (Brodbeck et al, 2020; Har-shai Yahav & Zion Golumbic, 2021). The prerequisite of background stream segregation might be highly distinctive features, which results in categorical differences, such as different gender of speakers; but this background stream segregation might be unique to speech perception.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies also confirmed the recognition of some words from a background speech stream, even if the background consisted of multiple voices (Dekerle et al, 2014). Furthermore, signs of spectro-temporal and linguistic processing of task-irrelevant speech streams were found in the auditory cortex, left inferior cortex, and posterior parietal cortex (Brodbeck et al, 2020; Har-shai Yahav & Zion Golumbic, 2021). The prerequisite of background stream segregation might be highly distinctive features, which results in categorical differences, such as different gender of speakers; but this background stream segregation might be unique to speech perception.…”
Section: Discussionmentioning
confidence: 99%
“…In interpreting the results of our study, it is important to bear in mind that the neural metric of speech tracking used here (envelope-following response) primarily captures the acoustic representations of input in auditory cortex (Ding and Simon 2012a; Mesgarani and Chang 2012; Zion Golumbic et al 2013; Fiedler et al 2019a; Har-shai Yahav and Zion Golumbic 2021). Therefore, the current results should not be taken as an exhaustive description of all the ways in which attention may affect neural processing of speech.…”
Section: Discussionmentioning
confidence: 99%
“…This ‘ground-truth’ problem is extremely difficult to address empirically, since we lack a reliable readout of an individual’s internal allocation of attention. Unfortunately, most behavioural and neural measures used in in Selective Attention paradigms cannot provide sufficient temporal resolution to indicate the momentary locus of attention and/or how well task-irrelevant speech has been processed (Har-shai Yahav and Zion Golumbic 2021). While some attempts have been made at utilizing advanced analytical approaches to achieve real-time measures of attention (Miran et al 2018; Jaeger et al 2020), these studies are still limited by the lack of access to the true internal state of attention.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations